Analysis of Opportunities and Challenges of Podcasts as a Means of Da'wah in the Digital Era: Analisis Peluang Dan Tantangan Podcast Sebagai Sarana Dakwah Dalam Era Digital - Izzudin Hitimala (Institute of Educational, Research, and Community Service, 2023)
This research investigates the opportunities and challenges associated with the use of podcasts as a means of da'wah in the digital era. The aim is to understand the potential of podcasts in reaching a wider audience, the flexibility of production, and the interaction provided to the audience. Additionally, this research also aims to identify challenges such as intense competition, resource-intensive production, regulations, and potential negative impacts. The research method used is library research to analyze various literature sources with in-depth analysis to dissect the research problem formulation. The results of this research reveal that podcasts have great potential in spreading religious and moral messages to a diverse audience geographically. The flexibility of production and interaction with the audience are also positive aspects. However, the da'wah community needs to address intense competition and ensure adequate production quality. Applicable regulations must be understood, and da'wah presenters must communicate carefully to avoid negative impacts. In order to harness the potential of podcasts as an effective da'wah tool, careful content planning, strong promotion, in-depth regulatory understanding, and technology trend monitoring are key in addressing the existing challenges. Podcasts can be a powerful means of da'wah in this digital era if managed well and wisely